Establishment Lockout Tagout (LOTO) quality manual at Sri Aman Fabrication and Industrial Trading Sdn Bhd - Mohammad, Zulhaimi; Kadoura, Ahmed Mohamed; Alkbir, M.F.M.; Kosnan, Shahrul Effendy; Safie, Sairul Izwan (Auricle Global Society of Education and Research, 2024)
Lockdown Tagout is a crucial aspect of occupational safety. In fact, it is essential to protect employees and workers near the machinery and equipment they use, maintain, and service. Still, there was information in this study regarding a LOTO system to create a LOTO quality manual at Sri Aman Fabrication and Industrial Trading Sdn Bhd. Observation and interviews have been done in order to collect data from all respective failures. The current study encompassed the entire framework development process, including variable identification, Failure Mode and Effect Analysis (FMEA), implementation of the LOTO quality manual, LOTO training programme, and procedure, and, at the end, the creation of an initial conceptual model for a sustainable maintenance framework.